Virtues of Teachers - ฉิ่นไพศาล, นิทรา; วฑฺฒจิตฺโต, พระครูสุจิตรัตนากร (Journal of Educational Review Faculty of Education in MCU, 2018)
The rapid changes in social environment affect teachers’ behaviors and there is critic on teacher’s profession. However, teacher is one of the most important components for the country development. Therefore the teacher’s ethics should be improved because the teacher and ethics cannot be separated. The teachers without ethics and virtues are similar to monks without discipline. The teacher’s ethics are quality of goodness, rightfulness and appropriateness embedded in the teacher’s mind and that will enforce teacher to perform the duty appropriately and effectively. In Buddhism, there are many principles concerning teachers, and some will be shown here. The teacher must have Kalyanamitta Dhamma: 1. Piyo or lovable, 2 Guru or respectable, 3. Bhavaniyo or adorable, 4.Vatta Ca or being a counselor, 5. Vacanakkhamo or being a patient listener, 6.Gambhiranca Katham Kata or able to deliver deep discourses, and 7. No Catthane Niyojaye or never exhorting groundlessly.